Bridging the Gap: Aligning Vocational Graduates’ Competencies with Employer Expectations Using the KSAO Model - Ming Foong, Lee; Zheng, Jinhua; Zhang, B.L. (Journal of Technical Education and Training, 2025)
In response to growing concerns regarding vocational college students' career issues, this study uses the KSAO model to investigate the competency gap between upper vocational accounting majors and employer expectations.  This study identifies differences across important dimensions : knowledge (K), skills (S), ability (A), and other attributes (O) by using two set of instrument with four major indicators and 32 secondary indicators. The findings indicate that the satisfaction ratings of employers regarding students' core competencies and the graduates' self-assessments of their core competencies across all KSAO elements exhibit high mean scores. Findings show that the satisfaction rating of employers on the core competencies of students' employment in descending order is other attributes > ability > knowledge > skills. On the other hand, graduates perceived themselves on the core competencies of students' employment in descending order:  knowledge > other attributes > skills > ability. There is a mismatch between employers’ perception and the graduated perception of the core competencies of students' employment, and it is proven by the independent sample t-test. A strategy to enhance the core competencies of higher vocational accounting students through SWOT analysis was recommended as guidance for vocational institutions in strengthening talent development strategies and student core competencies, thereby contributing to bridging the gap between education and workforce needs.